Bifunctional acidic ionic liquid-catalyzed decarboxylative cascade synthesis of quinoxalines in water under ambient conditions. Issue 20 (26th August 2021) - Liu, Shanshan; Zhang, Pingjun; Zhang, Yuanyuan; Zhou, Xianying; Liang, Jiahui; Nan, Jiang; Ma, Yangmin
Abstract : An acid-functionalized ionic liquid (IL)-catalyzed cascade decarboxylative cyclization of 2-arylanilines with α-oxocarboxylic acids was developed. Abstract : An acid-functionalized ionic liquid (IL)-catalyzed cascade decarboxylative cyclization of 2-arylanilines with α-oxocarboxylic acids was developed. This approach offered a sustainable and practical pathway to afford a library of quinoxalines in water under ambient conditions. This protocol tolerated various kinds of functional groups and could be easily scaled-up. The developed method featured a recyclable catalytic system, environmentally friendly reaction conditions, simple operation, and a practical workup procedure, which represented the potential to streamline quinoxaline synthesis in industry. A possible mechanism involving a dual activation strategy to promote both decarboxylation and cyclization processes was proposed.